Optimizing CRISPR/Cas9 for the Diatom Phaeodactylum tricornutum - Stukenberg, Daniel; Zauner, Stefan; Dell’Aquila, Gianluca; Maier, Uwe G. (Frontiers in Plant Science, 2018)
CRISPR/Cas9 is a powerful tool for genome editing. We constructed an easy-to-handle expression vector for application in the model organism Phaeodactylum tricornutum and tested its capabilities in order to apply CRISPR/Cas9 technology for our purpose. In our experiments, we targeted two different genes, screened for mutations and analyzed mutated diatoms in a three-step process. In the end, we identified cells, showing either monoallelic or homo-biallelic targeted mutations. Thus, we confirm that application of the CRISPR/Cas9 system for P. tricornutum is very promising, although, as discussed, overlooked pitfalls have to be considered.